Development of a Modular Unit of a Higher Level Framework or Tool for Basic Programming Course Teaching Through E-Learning Mode - Radhika Pathi; G.V. Rao; P. Rama Krishna; P. Bharath Kumar (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This paper reports about the development of a modular unit of a higher level framework or tool whose intended objective is the creation of animated lessons for basic programming (CS1) course in computer science discipline with visual aids. The goal of such lessons is to address the difficulties faced by the novice programmers in CS1 course.This module here after referred to as ‘type writer’allows instructors to render programmes or code snippets in a live typing manner as opposed to their sudden or en-block placement on the presentation area like a Power Point Slide; a commonly used approach in the present day eLearning.This project is planned to be executed in two stages and ‘type writer’ is the outcome of the first stage. This would be combined with another two modules that are planned to be developed in the second stage, to make the complete tool. The entire tool would be developed in Action Script 3.0 language that works on Adobe Flash Platform.